Health benefits of aerobic exercise: known mechanisms and research potential - Yu. L. Begrambekova; Ya. A. Orlova (Кардиоваскулярная терапия и профилактика, 2021)
The pandemic of noncommunicable diseases, which is currently one of the main threats to health and well-being of mankind, makes us look for ways to prevent their development early. Low cardiorespiratory endurance due to a sedentary lifestyle is associated with high cardiovascular risk, all-cause and cancer mortality. Skeletal muscles are the most important secretory organ and is characterized by outstanding metabolic performance and endurance. Exercise-induced low-dose stress contributes to mitochondrial biogenesis and remodeling of not only the muscular system, but also other systems involved in maintaining muscle activity, including regulating glucose and fat metabolism, maintaining immunity, and stimulating angiogenesis. These and other effects of physical activity are implements through the myokine system discovered in recent years. Shutting off the paracrine, exocrine and endocrine functions of muscles cannot be replenished in any other way and leads to disruption of vital adaptive processes. This review describes currently available evidence of unique role of aerobic physical activity in maintaining the human health, as well as to define the chain of pathological reactions during physical inactivity. The search was carried out in the Medline and PubMed Central databases for the keywords: cardiorespiratory endurance, non-communicable diseases, maximum oxygen consumption, myokines, interleukin-6, aerobic exercise.